NOOTROPIC EFFECT OF COMPLEX PHYTOREMEDY «NOOPHYT» EXTRACT - N. Ts. Bazarova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
In experiments on white rats (Wistar line) it was found that the dry extract of phytoremedy «Noophyt» pronounced nootropic effect. «Noophyt» extract in a volume of 0,2 and 0,5 ml/100 g simulated the development of conditioned reflexes of active and passive avoiding and caused to the saving of a memorable trace in the kept away terms after training оf intact animals and also in a volume of 0.5 ml/100g has a marked effect on the background antiamnesic skopolaminovoy amnesia.